The Rademacher System in Function Spaces 2020
DOI: 10.1007/978-3-030-47890-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Rademacher Chaos in Symmetric Spaces

Abstract: We study density estimates of an index set A, under which unconditionality (or even a weaker property of the random unconditional divergence) of the corresponding Rademacher fractional chaos..,j d )∈A in a symmetric space X implies its equivalence in X to the canonical basis in ℓ 2 . In the special case of Orlicz spaces L M , unconditionality of this system is also equivalent to the fact that a certain exponential Orlicz space embeds into L M .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The next step in the study of the behaviour of the Rademacher chaos in symmetric spaces was made by the authors of the present paper by employing the important concept of combinatorial dimension developed earlier by Blei (see [10]- [14]). Namely, in [9] it was shown that the above results in [7] and [8] can be extended to a non-complete chaos…”
Section: § 1 Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…The next step in the study of the behaviour of the Rademacher chaos in symmetric spaces was made by the authors of the present paper by employing the important concept of combinatorial dimension developed earlier by Blei (see [10]- [14]). Namely, in [9] it was shown that the above results in [7] and [8] can be extended to a non-complete chaos…”
Section: § 1 Introductionmentioning
confidence: 89%
“…Indeed, by (8) and in view of Bernstein's inequality (see for example, [35], Ch. 1, § 6, formula (42), or [2], Proposition 1.2), we have, for any t ∈ [0, 1] and λ > 0,…”
Section: Systems Of Random Unconditional Convergence and Divergence Inmentioning
confidence: 99%
See 3 more Smart Citations